PENGARUH UKURAN DEWAN KOMISARIS DAN KEPEMILIKAN ASING TERHADAP LUAS PENGUNGKAPAN CSR - Chen, Ming (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study aims to determine the effect of the size of the Board of Commissioners and Foreign Ownership on the Extent of CSR Disclosure. This study was tested using multiple regression. The sample is a Manufacturing company listed on the Indonesia Stock Exchange. The study period for 3 years fr: m 2014 until 2016. The results of the study found that the size of the board of commissioners influences the extent of CSR disclosure while Foreign Ownership does not affect the wide range of CSR disclosure.